Precision Agriculture Technologies for Early Detection of Crop Pests and Diseases - Chattopadhyay, Dipanwita; Balachandra, Y.; P, Ashoka; Pagire, Kailas Sampat; Sahu, Thaneshwar Kumar; Panotra, Narinder; Manisankar, G.; Charitha, Kurru; Singh, Bal veer (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Crop pests and diseases pose significant challenges to agricultural productivity and food security worldwide. Traditional methods for detecting and managing these threats often rely on manual scouting and blanket pesticide applications, which can be labor-intensive, time-consuming, and environmentally harmful. Precision agriculture technologies offer promising solutions for early detection and targeted management of crop pests and diseases. This review article provides a comprehensive overview of the latest precision agriculture tools and techniques for monitoring crop health, detecting pests and diseases, and guiding site-specific interventions. Key technologies discussed include remote sensing, proximal sensing, machine learning, robotics, and Internet of Things (IoT) sensors. The article highlights the potential of these technologies to improve the timeliness, accuracy, and efficiency of pest and disease detection while reducing reliance on chemical inputs. It also discusses the challenges and opportunities for integrating these technologies into current agricultural practices and extension services. The review concludes with recommendations for future research and development to advance precision agriculture solutions for sustainable crop protection.